Oxidized Starch/CMC based Biofilm: Synthesis and Characterization (Physical Sciences and Technology, 2024)
Starch-based biopolymers, derived from renewable resources, offer a sustainable alternative to plastic packaging. They are biodegradable, versatile, and increasingly cost-effective, though challenges remain in improving their properties. This research centered on developing a biodegradable biofilm from oxidized corn starch and carboxymethylcellulose, using succinic anhydride as a crosslinker. The biofilm’s mechanical strength, water absorption, and biodegradability were evaluated and compared to a commercial biopolymer. The biofilm exhibited a strength of 0.78 MPa, absorbed 0.21% water, and had a biodegradability rate of 0.008%. These findings suggest that the biofilm has significant potential for industrial applications, particularly in the biofilms and bioplastics sector. This study contributes to the ongoing global efforts to create sustainable alternatives to conventional plastic packaging, a critical aspect of environmental preservation. The promising characteristics of the synthesized biofilm indicate its potential to significantly influence the future of packaging materials. This research marks a progressive step in the pursuit of sustainable packaging solutions.